MODELLING OF EXTREME FLOODS ON EXAMPLE OF MOUNTAIN REGIONS OF UKRAINE - Gopchenko, E.; Ovcharuk, V.; Shakirzanova, J.; Goptsiy, M.; Traskova, A.; Shvec, N.; Serbova, Z.; Todorova, О. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
In the conditions of modern changes of climate both in Ukraine and in the world on the whole, probability of the extreme hydrological phenomena rises substantially, in particular, catastrophic floods of different origin. The analysis of flood distribution on the territory of Ukraine shows that an overwhelming amount of destructive floods happened in Ukrainian Carpathians, where they are the characteristic feature of the hydrological mode of the rivers. Floods which are observed on the rivers of Crimean Mountains also, for individual years, had catastrophic character. For determination of water discharge calculations in the period of floods on the mountain rivers of Ukraine authors offer a scientific-methodical base which is based on modern scientific achievements in area of theoretical and applied hydrology. Fundamentally new in the proposed model is the separation of factors of forming and transformation of flood flow on slopes and in a river-bed network. The method of numeral solution of task was developed for nonmeasureable descriptions of floods and it found practical application. As a result, the numerical values of the main components of the slope inflow are obtained: the layers of runoff for the flood of 1% probability and the duration of the slope inflow, which are generalized over the territory, taking into account the influence of intrazonal and azonal factors (forestation, mean height of the catchments and karst) and coefficient of time nonuniformity of slope inflow, which are averaged within the studied regions. The process of transformation of slope inflow into channel runoff is described with the help of transformation functions that take into account the time of channel run-up and flood plain regulation. The accuracy of determining the maximum modules of the runoff of 1% probability of exceeding depends on the accuracy of the initial information, which makes it possible to recommend the proposed methodology for practical use in order to increase the level of hydraulic engineering projects and water resources management on the mountain territories of Crimea and Carpathians.
Keywords: scientific-methodical base; maximal runoff; rain floods; mountain rivers